Problems of monitoring critical elements of scaffolding - Amin Ramezantitkanloo; Dariusz Czepiżak; Michał Pieńko (Archives of Civil Engineering)
Scaffolds are temporary structures that include anchors, elements, and platforms that are used during the construction of steel or concrete structures to support equipment or workers at height. Since these structures have aimed to guarantee safety and support workers at heights, the stability of scaffold systems is of significant importance. These systems have some disadvantages. For example, they are sensitive to vibrations. This feature reduces their stability under service-, cyclic-, or earthquake loadings. Furthermore, the vibrating nature of scaffolds can impose additional axial loads and consequently additional moment loads on the scaffold columns and decrease the safety of workers and increase the accidents of use of them. In this paper, a review of some research has been performed that aimed to solve this problem and improve the stability of scaffolds. These articles have investigated the behaviour of anchors and joints and the influence of imperfections and inaccuracies on scaffolds. A summary of research has been presented that has proposed new methods for predicting the behaviour, damage, and collapse of scaffolds using some structural health monitoring (SHM) methods. Finally, the research gaps and limitations of previous studies have been investigated, with a focus on monitoring and solving the problems of the scaffolds and critical elements so that these problems can be solved and evaluated in future studies.